Impact of Contextual Predictors on Value-Added Teacher Effectiveness Estimates - Ismail Aslantas (MDPI AG, 2020)
It is widely believed that the teacher is one of the most important factors influencing a student's success at school. In many countries, teachers' salaries and promotion prospects are determined by their students' performance. Value-added models (VAMs) are increasingly used to measure teacher effectiveness to reward or penalize teachers. The aim of this paper is to examine the relationship between teacher effectiveness and student academic performance, controlling for other contextual factors, such as student and school characteristics. The data are based on 7543 Grade 8 students matched with 230 teachers from one province in Turkey. To test how much progress in student academic achievement can be attributed to a teacher, a series of regression analyses were run including contextual predictors at the student, school and teacher/classroom level. The results show that approximately half of the differences in students' math test scores can be explained by their prior attainment alone (47%). Other factors, such as teacher and school characteristics explain very little the variance in students' test scores once the prior attainment is taken into account. This suggests that teachers add little to students' later performance. The implication, therefore, is that any intervention to improve students' achievement should be introduced much earlier in their school life. However, this does not mean that teachers are not important. Teachers are key to schools and student learning, even if they are not differentially effective from each other in the local (or any) school system. Therefore, systems that attempt to differentiate "effective" from "ineffective" teachers may not be fair to some teachers.